2021
DOI: 10.1186/s40246-021-00332-5
|View full text |Cite
|
Sign up to set email alerts
|

Performances of NIPT for copy number variations at different sequencing depths using the semiconductor sequencing platform

Abstract: Objective To evaluate the performance of noninvasive prenatal testing (NIPT) and NIPT-PLUS for the detection of genome-wide microdeletion and microduplication syndromes (MMSs) at different sequencing depths. The NIPT sequencing depth was 0.15X, and the data volume was 3 million reads; the NIPT-PLUS sequencing depth was 0.4X, and the data volume was 8 million reads. Methods A cohort of 50,679 pregnancies was recruited. A total of 42,969 patients opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
3
22
2
Order By: Relevance
“…Surprisingly, we did observe that the larger the CNV size, the lower the PPV. While some studies have reported that the PPV of CNVs > 10 Mb is the lowest [15,24], we could not obtain strong evidence to explain this strange problem. We conjecture that this may be attributed to the interference of chromosomal location of CNVs with the PPV estimation.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Surprisingly, we did observe that the larger the CNV size, the lower the PPV. While some studies have reported that the PPV of CNVs > 10 Mb is the lowest [15,24], we could not obtain strong evidence to explain this strange problem. We conjecture that this may be attributed to the interference of chromosomal location of CNVs with the PPV estimation.…”
Section: Discussioncontrasting
confidence: 91%
“…Only a few reports have assessed the detection rate of some varieties of MMs. Our study reported that the PPV for NIPS with low-coverage sequencing depth for detection of fetal CNVs (38.5%) was higher than that reported in similar studies, such as those reported by Yang (30.96%) [24], Hu (36.11%) [16] and Chen (28.99%) [15]. Recently, it has been reported that the PPV could improve with high-coverage sequencing.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The detection of chromosome abnormalities and pCNVs in pregnancies with different indications was analysed in our study. Growing evidence has revealed that NIPT dramatically improves the detection of common aneuploidies and pCNVs 25 , 26 . Consistent with these reports, the detection rates of aneuploidies and pCNVs in pregnancies with an increased NIPT risk were elevated significantly in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most providers disclose CNVs that are expected to be clinically relevant and potentially actionable. The positive predictive value (PPV) for CNVs is significantly lower than that of common trisomies [ 3 , 4 ], but it is still higher than that of sex chromosomal aneuploidies, particularly monosomy X [ 5 ]. Since the vast majority of cell-free (cf) DNA is derived from the maternal genome, genome-wide approaches primarily reveal maternal imbalances with much higher resolution than fetal imbalances, even with low-coverage genomic sequencing.…”
Section: Introductionmentioning
confidence: 99%